1993
DOI: 10.1017/s0020743800059274
|View full text |Cite
|
Sign up to set email alerts
|

Was al-Shafii the Master Architect of Islamic Jurisprudence?

Abstract: During the last three or four decades, modern scholarship has increasingly come to recognize Muhammad Ibn Idris al-Shafi c i (d. 820) as having played a most central role in the early development of Islamic jurisprudence. It was Joseph Schacht who, more than anyone else, demonstrated Shafi c i's remarkable success in anchoring the entire edifice of the law not only in the Qur'an, which by his time was taken for granted, but mainly, and more importantly, in the traditions of the Prophet. 1 Shafi c i's prominent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(10 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…Indeed, (Hallaq 1993) pointed out through the close examination of manāqib and biographical sources that "Shafi'i's prominent status has been further bolstered by the fact that he was the first Muslim jurist ever to articulate his legal theory in writing, in what has commonly become known as al-Risāla." However, he goes on to say that this book "and the theory that it embodied had very little if any effect during the 9th century; and that the image of Shafi'i as the founder of uṣūl al-fiqh was a later creation".…”
Section: Introduction 1 Methods Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, (Hallaq 1993) pointed out through the close examination of manāqib and biographical sources that "Shafi'i's prominent status has been further bolstered by the fact that he was the first Muslim jurist ever to articulate his legal theory in writing, in what has commonly become known as al-Risāla." However, he goes on to say that this book "and the theory that it embodied had very little if any effect during the 9th century; and that the image of Shafi'i as the founder of uṣūl al-fiqh was a later creation".…”
Section: Introduction 1 Methods Of the Studymentioning
confidence: 99%
“…Moreover, according to Hallaq, his image "as the founder of this discipline began to grow only from the beginning the 10th century." As such, we have to pay attention that evaluations of al-Shāfi'ī have changed to some extent (Hallaq 1993, The Miḥna of Imām al-Shāfi'ī 587-599;Shāfi'ī 1961). For example, Chaumont considers al-Shāfi'ī as "the eponym, rather than the founder, of the Shāfi'ī school (madhhab)" (Chaumont 1995, 181).…”
Section: Introduction 1 Methods Of the Studymentioning
confidence: 99%
“…Any talk of Islamic or Muslim leadership without reference to the texts, and ultimately to the character, actions and sayings of the Prophet Muhammad, lack verstehen (Weber, 1978,pp. 8-9, 57), in the sense that they do not engage with the meaning structures recognised by Muslims throughout history (Hallaq, 1993). This is the key to clarifying our understanding of leadership in the Muslim world.…”
Section: The Metaphysical Foundations Of Rational-legal Authority In mentioning
confidence: 99%
“…3 In a 1993 article Wael Hallaq used the observation that al-Shāfiʿī's work differs in important respects from later works to deny the existence of a genealogical relationship between the Risāla and the classical genre of legal theory. 4 He argued instead that the Risāla is primarily a theoretical work whose aim is to establish the authority of hadith, while the discipline of legal theory concerns itself with theorizing the relationship between reason and revelation. His search in Ibn al-Nadīm's Fihrist for early works with the word uṣūl in the title having been unsuccessful, Hallaq concluded that there is no evidence of legal-theoretical literature before the generation of Ibn Surayj, a full century later.…”
mentioning
confidence: 99%